PENERAPAN ALGORITMA BOYER MOORE DALAM PERANCANGAN KAMUS ISTILAH PERTANIAN BERBASIS ANDROID - Fitriani Br. Manurung; Nelly Astuti Hasibuan; Natalia Silalahi (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
The process of selecting the North Sumatra Ambassador Language Finalists at the North Sumatra Language Hall is still subjective in that the assessment may not be based on established criteria or without looking objectively so that the selection process is carried out less precisely and the resulting decision is less satisfactory for the participants of the Ambassador Finalists North Sumatra Language. In this study, the authors used a decision support system with the Promethee II method to find the value of weights and criteria, and to find the final score or to find the finalist ranking of the North Sumatra Language Ambassador. Thus the Decision Support System is needed in order to help the North Sumatra Language Office in determining the Finalists of the North Sumatra Language Ambassador. To overcome these problems, it is necessary to build a decision support system application for the selection of North Sumatra Language Ambassador Finalists using the Promethee II method so that it can help and facilitate the North Sumatra Language Hall in making a decision to choose the North Sumatra Language Ambassador and the resulting decision is satisfactory.Keywords: Decision Support System, Language Ambassadors, Promethee Method ii